The Low- to High-Tech Assistive Technology for the Learning Process of Students with Special Needs in Inclusive Classrooms : A Literature Review - Maringgar Hangesti Putri (Dinas Pendidikan, Pemuda dan Olahraga Daerah Istimewa Yogyakarta, 2025)
This study aims to systematically review the use of assistive technology in the learning process of students with special needs in inclusive classroom settings. Assistive technology covered in this research ranges from low-tech tools (such as picture communication boards) to high-tech devices (such as adaptive learning applications and computer-assisted communication systems). Using a literature review method, this study analyzes scholarly publications from 2015 to 2025, focusing on the effectiveness, challenges, and implementation strategies of assistive technology in inclusive education. The findings indicate that assistive technology plays a crucial role in enhancing accessibility, participation, and learning outcomes for students with special needs. However, its success is highly influenced by teacher preparedness, appropriate technology selection, and institutional support. This study offers insights and recommendations for educators and policymakers to optimize the use of assistive technology in fostering inclusive and adaptive learning environments.